Financial inclusion and its determinants for Latin America period: 2004-2020 - Villalta Romero, Dante (Universidad Francisco de Paula Santander, 2024)
Financial Inclusion contributes to improving the economic growth and well-being of the population. This document analyzes the factors that explain the determinants of financial inclusion in Latin American countries, allowing economic agents to increase the conditions of access, use and depth, which is influenced by a set of variables that are grouped into six macroeconomic factors., banking, socioeconomic, governmental, labor and technological. For this, the estimation methodology has been used using a fixed-effects panel data model, which includes 14 countries in the Latin American region and a study period ranging from 2004-2020. The results of the study show that there is a positive correlation between some of the factors used in the model, being the most significant macroeconomic, banking, socioeconomic, governmental, and labor factors. Regarding the technological factors, of the three variables, only cellular telephony is significant, however, it adds significance to the general model. In conclusion, we can affirm that the chosen factors explain the determinants of financial inclusion in the case of Latin America.